Defisiensi Vitamin D dan Paparan Sinar Matahari yang Berkaitan dengan Defisiensi Vitamin D pada Tenaga Kesehatan COVID-19 - Maria Eka Patri Y; Noor Diah Erlinawati (Jurnal Keperawatan Silampari, 2021)
This study aims to determine the description of vitamin deficiency and sun exposure to vitamin D deficiency in COVID-19 health workers in Bengkulu City. This research method is a cross-sectional or cross-sectional descriptive study using a survey or exploratory approach. The results showed that the frequency distribution of the characteristics of the research subjects was mostly 40 years old, with the most occupations being nurses. Most of the disease history was allergies, and 75% of the subjects had no history of the disease. A history of positive confirmation of COVID-19 is 16%. The number of subjects with a history of exposure to the sun with appropriate recommendations was 48%, and those with a history of exposure to more than the recommendation were 27%. There are still 24% of subjects who have low sun exposure, which is under 15 minutes. Based on the examination results of vitamin D levels, most of the research subjects who were health workers experienced 59.5% deficiency and 37.8% insufficiency. The relationship between sun exposure and blood Vitamin D3 levels p = 0.175 (fisher exact test) The results of the Kendall's tau_b correlation are r = 0.047, p = 0.722, age vs vitamin D levels are r = 0.246, p = 0.141, and bodyweight vs vitamin D levels D is r=0.312, p = 0.060. Based on the examination results of vitamin D levels, most of the research subjects who were health workers experienced 59.5% deficiency and 37.8% insufficiency. In conclusion, the relationship between sunlight, age, and body weight with vitamin D levels showed that it was not significant, but this indicated that other variables influenced the deficiency state of health workers. Keywords: COVID-19, Vitamin D, Sun Exposure